2006
DOI: 10.1063/1.2168019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substitutions on the thermoelectric figure of merit of half-Heusler phases at 800 °C

Abstract: The merit of thermally stable MNiSn (M=Ti, Zr, Hf) half-Heusler phases, as n-type thermoelectric materials, for high-temperature power generation has been examined. Sb doping at the Sn site is shown to increase both the figure of merit, ZT, and the temperature at which ZT is maximized. The benefits of increased alloying at the M and Ni sites, on the thermal conductivity and thermoelectric transport properties, have also been investigated. The thermoelectric figure of merit, ZT∼0.8 at T∼800°C, for select Sb-dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
142
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(157 citation statements)
references
References 10 publications
9
142
0
2
Order By: Relevance
“…Compared with the PbTe or LAST systems, half-Heusler compounds are more environmentally benign and hence have attracted increasing levels of interest [70][71][72][73][74]. Half-Heusler compounds are crystallized in the MgAgAs-type structure with space group F4 ‾3m, which can be regarded as two interpenetrating cubic face-centered-cubic …”
Section: Half-heusler Compoundsmentioning
confidence: 99%
“…Compared with the PbTe or LAST systems, half-Heusler compounds are more environmentally benign and hence have attracted increasing levels of interest [70][71][72][73][74]. Half-Heusler compounds are crystallized in the MgAgAs-type structure with space group F4 ‾3m, which can be regarded as two interpenetrating cubic face-centered-cubic …”
Section: Half-heusler Compoundsmentioning
confidence: 99%
“…[1][2][3][4]30 X-ray diffraction pattern for the annealed samples is shown in Figure 1. The need for long term annealing indicates large barriers for long-range atomic diffusion.…”
mentioning
confidence: 99%
“…In the present work, it is shown that small concentrations of vanadium substituted to the group IVB metal site of Hf 0.75 Zr 0. 25 NiSn have the effect of increasing the density of states at the Fermi level, thereby augmenting the thermoelectric properties of that compound at temperatures up to 650 K. Measurements of electrical resistivity and Seebeck coefficient were carried out simultaneously from room temperature to 1100 K on a custom apparatus that has been described previously [18] and were performed during both the heating and cooling cycles. Electrical resistivity values varied less than approximately 1% from heating to cooling cycle, while Seebeck coefficient measurements of the different cycles were consistent to within 5% of one another.…”
mentioning
confidence: 99%